Stateczność Wstępnie Sprężonego Walca Kołowego - E. Złatanowa; Z. Wesołowski (Engineering Transactions)
A simple circular cylinder is deformed in a finite way by the adding or cutting out of a wedge with an arbitrary angular aperture and by restoring the cohesion of the material. The stability of the cylinder so formed is investigated by using the method of small deformations superposed on the finite deformations. The condition of loss of stability is given with a limitation to the case when the additional deformation is plane. The critical deformation is calculated for Mooney’s material.